Technology Ethics in Public Service: Envisioning the Role of the Techno-Ethicist. (4th March 2023) - Baracskay, Daniel
Abstract: In terms of technological progress, students of public administration confront a challenging dilemma where normative reflection in the realm of technology ethics has not kept pace with the rapidity and magnitude of technological advancement. Consequently, this necessitates further reflection on how to best apply aspects of ethical behavior to the development and usage of technology in the public sector. The significant role of the technology ethics in public service has received meager consideration in the literature, lacking a theoretical foundation that can help guide practitioners (as techno-ethicists) through rapid transitions in technological progress. Using the philosophy of technology literature, this article seeks to address this gap in public administration theory by considering first, how technological advancements affect the nature of didactic power relationships between the public and government; and second how the concept of technological nonneutrality is framed as a basis for structuring what obligations public administrators have when adopting and using technology in public service. This includes reflection upon the expanding role of newer technologies such as Artificial Intelligence in reshaping the nature of government-society relationships. Framing techno-ethical principles in theoretical dialogue prompts greater awareness for how practitioners may effectively respond as moral agents to rapidly changing technological advancements.